Coming In: Queer Narratives of Sexual Self-Discovery - Rosenberg, Shoshana (Routledge, 2018)
© 2018, © 2018 Taylor & Francis. Many models of queer sexuality continue to depict a linear narrative of sexual development, beginning in repression/concealment and eventuating in coming out. The present study sought to challenge this by engaging in a hermeneutically informed thematic analysis of interviews with eight queer people living in Western Australia. Four themes were identified: “searching for identity,” “society, stigma, and self,” “sexual self-discovery,” and “coming in.” Interviewees discussed internalized homophobia and its impact on their life; experiences and implications of finding a community and achieving a sense of belonging; the concept of sexual self-discovery being a lifelong process; and sexuality as fluid, dynamic, and situational rather than static. The article concludes by suggesting that the idea of “coming in”—arriving at a place of acceptance of one’s sexuality, regardless of its fluidity or how it is viewed by society—offers considerable analytic leverage for understanding the journeys of sexual self-discovery of queer-identified people.